TELEHEALTH BEYOND DISPARITIES & DIVIDES : Rural care practitioners’ adoption of telehealth: a case study - Cheema, Shazada; Robertsson, Emelie (Umeå universitet, Institutionen för informatik, 2023)
Telehealth in rural and underserved areas are increasing rapidly due to centralization and cutbacks in healthcare. Since many telehealth studies has a patient-centered focus or organizational perspectives, we find a gap in research regarding practitioners' view in the unique contexts of rural areas. The question we seek to answer is how rural care providers experience telehealth solutions and what factors influence the adoption of its use. A mixed method case study with an interpretative approach is employed, examining a sample of rural cottage hospitals and their healthcare personnel in Northern Sweden. Data is collected through interviews, observations, and an online survey. Our thematic analysis reveals crucial connections between urban and rural settings causing sociocultural barriers. Education and tailored telehealth solutions considering the uniqueness of rural areas are thus recommended. Flaws in routines and interface design also contribute to the lack of interaction, thus the importance of user-centeredness with consideration of the urban-rural-divide and digital literacy disparities is highlighted. By offering insights into the practitioners' perceived experiences and the challenges they face, this study contributes to a more comprehensive understanding of telehealth implementation and utilization in rural areas and provides insights for improving user experience and adoption.